2021
DOI: 10.1186/s13071-021-04919-8
|View full text |Cite
|
Sign up to set email alerts
|

Burden of malaria in children under five and caregivers’ health-seeking behaviour for malaria-related symptoms in artisanal mining communities in Ghana

Abstract: Background Artisanal mining creates enabling breeding ground for the vector of malaria parasites. There is paucity of data on the effects of artisanal mining on malaria. This study assessed burden of malaria and caregivers’ health-seeking behaviour for children under five in artisanal mining communities in East Akim District in Ghana. Methods A cross-sectional study involving caregivers and their children under five was conducted in three artisanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
7
14
1
Order By: Relevance
“…This result was comparable to a study conducted in Arsi Negele, Ethiopia (22.8%) [ 16 ], Arba Minch Zuria District, South Ethiopia (22.1%) [ 17 ] and Nigeria (22.6%) [ 18 ]. In contrast, the prevalence determined in this study showed a lower prevalence of malaria than a study conducted in Mali (35.4%) [ 19 ], Ghana (43.0%) [ 20 ] and Cameron (28.8%) [ 21 ]. The low prevalence of malaria parasites in this study could be due to seasonal variations, as the current study was conducted in a minor malaria transmission season.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result was comparable to a study conducted in Arsi Negele, Ethiopia (22.8%) [ 16 ], Arba Minch Zuria District, South Ethiopia (22.1%) [ 17 ] and Nigeria (22.6%) [ 18 ]. In contrast, the prevalence determined in this study showed a lower prevalence of malaria than a study conducted in Mali (35.4%) [ 19 ], Ghana (43.0%) [ 20 ] and Cameron (28.8%) [ 21 ]. The low prevalence of malaria parasites in this study could be due to seasonal variations, as the current study was conducted in a minor malaria transmission season.…”
Section: Discussioncontrasting
confidence: 99%
“…Children whose mother/caregiver had never received malaria health education in the previous 6 months had a greater risk of infection than those whose mother/caregiver had received. This finding was also supported by the previous studies done in Uganda and Ghana [ 20 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…With a total of over 135,000 cases, and slightly over 1000 deaths, as at December 2021 [19], many in the country were indeed afraid of contracting the virus, which might have reduced their health seeking behaviour [17]. Malaria among children is still a significant public health issue in Ghana and one of the common reasons for hospital visits and admission [20,21]. With reports suggesting that malaria contributes significantly to hospital visits and admissions [21], it is likely that the COVID-19 pandemic and the subsequent restriction of movements could have decrease access to healthcare or delayed seeking care among children with malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria among children is still a significant public health issue in Ghana and one of the common reasons for hospital visits and admission [20,21]. With reports suggesting that malaria contributes significantly to hospital visits and admissions [21], it is likely that the COVID-19 pandemic and the subsequent restriction of movements could have decrease access to healthcare or delayed seeking care among children with malaria. In fact, the mere fear of contracting COVID-19, especially during the peak period of the COVID-19 pandemic, where the hospital was perceived by some parents as an infection hub, could significantly have contributed to high hesitancy in seeking appropriate healthcare for children with malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, adults living in urban areas are prone to malaria [20], therefore they must be considered when designing and implementing malaria control strategies. Although some previous studies have reported on the relationship between socio-demographic factors and bed net ownership, usage and malaria transmission among vulnerable sub-populations [4,17,21,22], such information is lacking among the urban adult population. This paper seeks to examine socio-economic and demographic factors affecting bed net ownership, usage and malaria transmission among adult patients seeking healthcare in two Ghanaian urban cities.…”
Section: Introductionmentioning
confidence: 99%